The limits of the grammatical rule in the metalinguistic treatment of the structures of a foreign language: the case of FFL - BENKOUIDER , Lamine (Journal of Social Sciences and Humanities, 2021)
This article presents the results of an analysis of the metalinguistic comments of a group of students on the choice of the temporal auxiliary in FFL. The objective of this study is to verify whether the use of the rule constitutes a handicap and a source of errors with regard to the metalinguistic treatment of FFL structures. In fact, learners resort to the rule each time that they carry out a metalinguistic analysis of the structures of the target language. However, the results of this study reveal the limits of the grammatical rule in such an operation.